1993
DOI: 10.1007/bf02639381
|View full text |Cite
|
Sign up to set email alerts
|

Mucin synthesis and secretion by cultured tracheal cells: effects of collagen gel substratum thickness

Abstract: We previously demonstrated that human tracheobronchial epithelial (TBE) cells synthesize mucin and form mucous granules in culture when they are maintained on a collagen gel (CG) substratum, but not on a plastic tissue culture surface or a thin collagen-coated surface (Wu et al., Am. J. Respir. Cell Mol. Biol., 3:467-478; 1990). This observation led us to examine the effects of CG thickness on cell growth and differentiation in primary human/monkey TBE cell cultures. Using the same CG preparation, culture dish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…However, the effect of collagen during the nasal cell culture is still controversial. It was reported that collagen gel, of which thickness was more than 1 mm could produce more pseudostratified cells (Robinson and Wu, 1993). However, in other reports (Werner and Kissel, 1995;Wu et al, 1985), collagen-coated supports provided similar or less cell growth and differentiation compared to uncoated supports.…”
Section: Sampling Technique For Nasal Cells From Tissuementioning
confidence: 87%
“…However, the effect of collagen during the nasal cell culture is still controversial. It was reported that collagen gel, of which thickness was more than 1 mm could produce more pseudostratified cells (Robinson and Wu, 1993). However, in other reports (Werner and Kissel, 1995;Wu et al, 1985), collagen-coated supports provided similar or less cell growth and differentiation compared to uncoated supports.…”
Section: Sampling Technique For Nasal Cells From Tissuementioning
confidence: 87%
“…The type of surface on which the cells are grown influences receptors as well as cellular architecture, two factors regulating gene expression and leading ultimately to the presentation of specific phenotypic characteristics (14). In addition, it appears that the epithelial cells will respond to secretory products from fibroblasts embedded in collagen gels (28,34).…”
Section: Discussionmentioning
confidence: 98%
“…However, increasing evidence suggests the need to further enhance in vitro culture systems with extracellular matrix (ECM) proteins to more closely simulate physiological environments. ECM (e.g., collagen I and IV, fibronectin, and laminin) are vital components of the cellular microenvironment in vivo and their use in vitro has been shown to promote cell growth and enhance expression of cell-specific morphology and function (28,34). Collagen I has been used to promote cell attachment and spreading, to expand cell populations rapidly, to grow cells in serum-free or serum-poor conditions, to investigate cell adherence, and to improve survival of primary ceils in culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, this could be improved by the adoption of certain strategies, such as the culturing of epithelial cells on a thicker threedimensional hydrogel matrix, 35 the use of the hydrogel matrix with the controlled release of agents known to induce a higher mucosecretory function, 36 the addition of a conditioned medium from respiratory fibroblasts, and the coculture of respiratory epithelial cells with respiratory fibroblasts 37 on our hydrogel matrix. These strategies could enable us to build epithelial tissue that closely resembles the composition of the natural epithelium.…”
Section: Discussionmentioning
confidence: 99%